Effect of Covid-19 Fear on Dental Anxiety Levels among Adult Patients in Periurban Islamabad - Sibtul Hassan, Ibraheem Khan, Haneena Khan, Ahmed Khan, Ayesha Khan, Hamza Waheed (Pakistan Journal of Medical & Health Sciences, 2022)
Objectives: To evaluate dental anxiety levels and fear of covid-19 and the correlation of dental anxiety with covid-19 fear. Methods: A cross-sectional study was conducted at Rawal General and Dental Hospital Islamabad, Pakistan using convenient sampling technique over a period of 6 months. A sample size of 167 adult (18yrs+) patients was taken. Data was collected through validated questionnaires in the OPD. Results: It was observed that people with higher fear of covid-19 had significantly higher dental anxiety levels and vice versa. The relation being significant (p <0.05). Conclusion: it was found that female patients had both high dental anxiety and fear of covid-19 while people aged 41yrs and above only had higher fear of covid-19 as compared to dental anxiety